Safety Design for the China Space Station - Wei Li; Yongqing Hou; Fengjiang An; Qiaoli Xia; Zhihai Li; Qiang Zhou (Space: Science & Technology, 2023)
The safety of a space station under normal and abnormal conditions can be ensured only by comprehensively identifying various hazards of the space station during its whole mission cycle and formulating control measures against each hazard. This paper describes the safety design process of the China Space Station, as well as detailed safety design measures for general hazards, fault hazards, dangerous events, and critical missions, so as to achieve safety goals as far as possible under the circumstances of limited resources and transportation capacity of the space station. The key work of safety design includes identification of hazard sources and dangerous events, formulation of safety control measures, and design of safety safeguard measures. Identification of hazards and hazardous events is based on both defined content in design schemes and previous on-orbit flight experience of manned spacecraft. The formulated safety control measures are based on analyzing each hazard to determine key links of safety control and formulate corresponding control measures for effective hazard control under minimum resource cost. In the case of a serious failure, the space station can remain safe within a certain time by its autonomous hazard disposal.